“What Your Parents Bequeathed You”: Perceptions of the Russian Language by Native Russian-Speaking Citizens of Lithuania - Лихачева, Алла Борисовна Борисовна (Slavistica Vilnensis, 2015)
The article, on the perceptions of the Russian language by native Russian-speaking citizens of Lithuania, is based on in-depth interviews conducted as part of the sociolinguistic projects “Language Use and Ethnic Identity in Lithuanian Cities” (2007–2009) and “A Sociolinguistic Map of Lithuania” (2010–2012). The perceptions of the Russian language by the interviewees in Lithuania are compared with analogous perceptions by native speakers in Russia that are discussed in the works of Russian researchers. The article contrasts the characteristics of the Russian language perceived by both categories of native speakers against those perceived by native Russian-speaking citizens in Lithuania alone. The attitudes towards the Russian language in Lithuania reflect the linguistic situation in the country and the “conscious” bilingualism of the native Russian-speaking interviewees. Although the respondents both in Russia and Lithuania claim that they value the aesthetic qualities of their mother tongue, in Lithuania the functional aspect of the Russian language is more emphasised. That is, for the Russian-speaking citizens of Lithuania the Russian language is significant and intimate in that it provides psychological comfort and the opportunity for more adequate verbal self-expression.
Keywords: Russian language; sociolinguistic data; in-depth interviews; respondents; perception of the Russian language